Control Simulation of Flapping-Wing Micro Aerial Vehicle Based on Multi-level Optimization Model Predictive Control - Zheng, Hongyu; Chen, Wengang; Xie, Fangfang (IEEE access, 2024)
In this paper, a control algorithm using multi-level optimization and model predictive control is proposed to solve the conflict between the computational cost and control accuracy of the flapping-wing micro aerial vehicle. First, a quasi-steady model is established to evaluate the aerodynamic forces and moments of the flapping-wing vehicle, and the forces and moments are then optimized to meet the control requirements based on classical model predictive control. Then an optimization module based on the quasi-steady model is introduced to optimize the kinematic parameters to achieve the optimal forces and moments, thus it decomposes the complex optimization problem of the classical model predictive control into two sub-problems. Compared with classical PID control and model predictive control, the response speed of the multi-level optimization model predictive control is effectively improved while maintaining high accuracy. Finally, the effectiveness of the control framework is validated by the control simulations of four examples of set-point and motion tracking control.